The Political-Legislative History of Science Textbooks of Brazil (Research, Society and Development, 2020)
The textbook strongly presents an editorial and state monopoly, denoting this material an instrument of statutory government policy maneuver, in addition to its function towards its pedagogical content. In this article, we present a legislative historical course of the science textbook with the bibliographic use and documents that governed its political course at a given moment in the legislative history of this didactic material with the purpose of a historical survey of its legislation of the twentieth and twenty-first centuries.